Methodology of assessing competencies of university graduates - R. B. Karaseva (Вестник СибАДИ, 2017)
The purpose of the article is the analysis of changes in the methodology for assessing the level of university graduates’ competence in accordance with the Federal law FL-273 "On education in the Russian Federation". There are analyzed the typical features of assessing competencies according to the SES-2 and FSES. It is justified that evaluative means should be used not only for assessment but also as a tutorial. On the basis of the conducted analysis it is concluded that the traditional forms of control should be improved and innovation forms must be adapted to the traditions of university education.